The Efficiency of Water Utilization in Local Legumes of Centrosema pubescens and Clitoria ternatea - N. K. A., Agustina; Candraasih, N. N.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The research aims to know the efficiency of water utilization in local legumes Centrosema pubescens and Clitoria ternatea with gave different concentration of water. The research was conducted for 12 weeks at the Green House Laboratory of Feeds, Faculty of Animal Science, Udayana University, Denpasar. The experimental design used in this research was completely randomn design (CRD) with split plot pattern. The main plot were the type of local legume, Centrosema pubescens (S) and Clitoria ternatea (C), while sub plot were the concentration of water 100% in field capacity (FC) (K1), 80% FC (K2), 60% FC (K3), 40% FC (K4). So, there were eight treatment combinations that were repeated five times with 40 experimental pots. The observed variables in the research were efficiency of water utilization, growth, plant’s production and characteristic grow of the plants. The research result showed that the local legumes were significant difference (P<0.05) in all variables except water utilization efficiency, plant height, number of leaves, dry weight of stem and root. Treatment of water concentration offered to the plants showed significant difference (P<0.05) on all variables except dry weight of leaves, root and the ratio of dry weight of leaves with stems. It can be concluded that the water level of 40% FC still be able to maintain the growth of local legumes as will as in the water concentration of 60% FC and 80% FC. Water concentration of 100% FC produced the highest yield on growth, production and characteristics grow of local legumes. The concentration water 40% FC gave the highest yield on efficiency of water utilization in local legumes. There was no interaction between the types of local legumes with different concentration of water. Keywords :   Centrosema pubescens, Clitoria ternatea, waterconcentration, efficiency of water utilization